Innovative lipid delivery systems in ruminant diets: the role of spray drying - de Oliveira, Thâmilla Thalline Batista; Ferreira, Thalia Catherine Sacramento; Tavares, Pedro Paulo Lordelo Guimaraes; Correia, Paulo Romano Cruz; Ribeiro, Cláudio Vaz Di Mambro; de Souza, Carolina Oliveira (Frontiers in Veterinary Science, 2025)
Ruminant nutrition faces multifactorial challenges, including genetic limitations, inadequate management practices, and biochemical and physiological constraints within the ruminal environment, which compromise nutrient utilization, animal productivity, and the environmental sustainability of production systems. One of the main bottlenecks is microbial biohydrogenation of lipids, which reduces the energy efficiency of diets and the bioavailability of essential fatty acids in ruminants. Spray-drying-based microencapsulation technology has been proposed as a strategy to protect lipids and bioactive compounds. However, comprehensive mechanistic reviews integrating scientific evidence, technological development, and zootechnical applicability are still scarce. This systematic review aims to map the landscape of scientific literature and technological records regarding the use of microencapsulated lipids and tannins in ruminant feeding, with an emphasis on spray-drying as the primary microencapsulation technique. The methodology involved bibliometric and technological analyses using The Lens database, covering publications and patents from 2015 to 2025. A total of 1,190 patents and 163 scientific articles on fatty acid microencapsulation were identified, highlighting efforts to improve thermal and oxidative stability, control ruminal release, and increase the dietary energy efficiency. Regarding tannins, 161 patents and 29 studies emphasized their role as co-microencapsulants with antioxidant, antimicrobial, and fermentation-modulating properties. A scarcity of applied studies in tropical areas was observed, along with a geographic mismatch between areas of high technological output, such as Europe, and major ruminant-producing countries, such as Brazil and India, highlighting the need for regionally adapted innovation. The mapped landscape underscores the strategic and multidimensional potential of microencapsulation technologies to mitigate nutritional losses, reduce enteric emissions, and promote efficient livestock systems. This review provides a critical and updated analysis of the trends, barriers, and opportunities, offering insights into the pathways for sustainable innovation in ruminant nutrition. These findings underscore the importance of aligning scientific advances with practical solutions in animal production.